Non-HLA gene effects on the disease process of type 1 diabetes: From HLA susceptibility to overt disease. (July 2015) - Lempainen, Johanna; Laine, Antti-Pekka; Hammais, Anna; Toppari, Jorma; Simell, Olli; Veijola, Riitta; Knip, Mikael; Ilonen, Jorma
Abstract: In addition to the HLA region numerous other gene loci have shown association with type 1 diabetes. How these polymorphisms exert their function has not been comprehensively described, however. We assessed the effect of 39 single nucleotide polymorphisms (SNP) on the development of autoantibody positivity, on progression from autoantibody positivity to clinical disease and on the specificity of the antibody initiating the autoimmune process in 521 autoantibody-positive and 989 control children from a follow-up study starting from birth. Interestingly, PTPN2 rs45450798 gene polymorphism was observed to strongly affect the progression rate of beta-cell destruction after the appearance of humoral beta-cell autoimmunity. Moreover, primary autoantigen dependent associations were also observed as effect of the IKZF4-ERBB3 region on the progression rate of β-cell destruction was restricted to children with GAD antibodies as their first autoantibody whereas the effect of the INS rs 689 polymorphism was observed among subjects with insulin as the primary autoantigen. In the whole study cohort, INS rs689, PTPN22 rs2476601 and IFIH1 rs1990760 polymorphisms were associated with the appearance of beta-cell autoantibodies. These findings provide new insights into the role of genetic factors implicated in the pathogenesis of type 1 diabetes. The effect of some of the gene variants is restricted to control the initiation of β-cell autoimmunity whereas others modify the destruction rate of the β-cells. Furthermore, signs of primary autoantigen-related pathways were detected. Highlights: SNP markers of Type 1 diabetes outside HLA region were analyzed in a follow-up cohort. Both initiation of autoimmunity and progression to clinical disease were studied. Effects of SNPs were usually restricted either to initiation or progression phase. Primary autoantigen specific gene effects were also detected.